2015
DOI: 10.1037/pha0000022
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory-based test of the relation between adolescent alcohol use and panic-relevant responding.

Abstract: A burgeoning literature supports a link between alcohol use and panic-spectrum problems (e.g., panic attacks, disorder) among adolescents, but the direction of influence has yet to be properly examined. From a theoretical perspective, panic-spectrum problems may increase risk for problematic drinking via affect regulation efforts (e.g., self-medication), and problematic consumption also may increase or initiate panic-relevant responding (e.g., learning or kindling models). The objective of the current investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 108 publications
(185 reference statements)
0
2
0
2
Order By: Relevance
“…Matthew and colleagues examined the relationship between alcohol use in adolescents and panic disorder – which typically emerges in late adolescence (Mathew, Norton, Zvolensky, Buckner, & Smits, 2011) and found that prior alcohol use among adolescents was associated with increased panic‐related symptoms using a hyperventilation challenge paradigm. In this cohort, the history of panic attacks was not associated with a desire to consume alcohol, suggesting that the ‘self‐medication hypothesis’ may not entirely explain this association (Blumenthal, Cloutier, Zamboanga, Bunaciu, & Knapp, 2015). The relationship between cannabis use and the development (and maintenance) of anxiety disorders has become clearer in recent years.…”
Section: Resultsmentioning
confidence: 73%
“…Matthew and colleagues examined the relationship between alcohol use in adolescents and panic disorder – which typically emerges in late adolescence (Mathew, Norton, Zvolensky, Buckner, & Smits, 2011) and found that prior alcohol use among adolescents was associated with increased panic‐related symptoms using a hyperventilation challenge paradigm. In this cohort, the history of panic attacks was not associated with a desire to consume alcohol, suggesting that the ‘self‐medication hypothesis’ may not entirely explain this association (Blumenthal, Cloutier, Zamboanga, Bunaciu, & Knapp, 2015). The relationship between cannabis use and the development (and maintenance) of anxiety disorders has become clearer in recent years.…”
Section: Resultsmentioning
confidence: 73%
“… Cloutier et al (2019) found that adolescent females with higher baseline social anxiety levels are more likely to consume their first alcoholic beverage within a year of exposure to an acute social stressor. However, anxiety symptoms alone do not necessarily lead to an increased urge to drink immediately in non-alcohol naïve adolescents ( Blumenthal et al, 2015 ), indicating that there are other factors at play in the relationship between adolescent alcohol consumption and anxiety that require further study (with access to alcohol likely being relevant). The same must be said of other common comorbidities of AUD, including MDD and conduct disorder due to the tendency to use alcohol as a coping method for psychological distress ( Zaso et al, 2021 ) and as a negative reinforcer among late-stage adolescents ( Obasi et al, 2016 ).…”
Section: Relationship Between Stress and Alcohol Usementioning
confidence: 99%
“…Piemēram, smēķētāji tic, ka smēķēšana var palīdzēt nomierināties, regulēt emocionālos un ķermeniskos stāvokļus (Mathew et al, 2011). Otrā hipotēze ir, ka alkohola un citu vielu lietošana ilgtermiņā vai atteikšanās lietot šīs vielas (absistences sindroms) rada fiziskas sajūtas, kas līdzinās panikas simptomiem, tādējādi ilgtermiņā un mijiedarbībā ar panikas traucējumu kognitīvo komponenti veicinot panikas simptomu turpmāko attīstību (Blumenthal et al, 2015).…”
Section: Panikas Simptomu Saistība Ar Alkohola Un Citu Atkarību Izraiunclassified
“…Zinātnieki noskaidroja, ka pusaudži, kas alkoholu lietojuši vairākas reizes pēdējā gada vai pēdējā mēneša laikā, salīdzinājumā ar tiem pusaudžiem, kas nekad nebija mēģinājuši vai bija pamēģinājuši, bet nav turpinājuši lietot alkoholu, pašnovērtējuma aptaujā atzīmēja biežākus panikas simptomus un kontrolētajā hiperventilācijas eksperimentā uzrādīja vairāk fizisko reakciju, kas saistītas ar panikas simptomiem (Blumenthal et al, 2012). Turklāt pusaudžu pašnovērtētā panikas simptomu vēsture pozitīvi korelēja ar panikas simptomiem hiperventilācijas eksperimenta laikā (Blumenthal et al, 2015). Pusaudžu panikas simptomiem netika atklāta saistība ar tabakas smēķēšanas biežumu (Blumenthal et al, 2012;.…”
Section: Panikas Simptomu Saistība Ar Alkohola Un Citu Atkarību Izraiunclassified